AESTHETIC ATTITUDE IN THE TEACHING OF MATHEMATICS - MIKAELIAN, HAMLET (Main Issues Of Pedagogy And Psychology, 2015)
In this paper we considerthe aesthetic attitude as a special case ofbinary and ternary relations. The article identifies some of the features ofternary aesthetic relations. It investigates problem of creating a healthy, positive aesthetic relations in the teaching ofmathematics, showing the role of subjective pupils’ health and especially the role ofthe teacher in the aesthetic sense.